The Role Of Economic groupings And Crisis In The Emergence Of The New Regionalism (Latakia University Journal - Economic and Legal Sciences Series, 2019)
After The Second World War, And The Contradictions It Created, Efforts Were Made To Remedy These Various Imbalances At Different Levels. The Reforms Were Based On Liberal Thoughts . Since The Capitalist Attempts To Renew Itself And Overcome These Problems, The Phenomenon Of  (Institutional, Geographical) Economic Groupings Has Emerged. In This Research, The Emphasis Will Be Placed On The Different Impact Of Crises To Determine Whether This Blocs Formed The Force Against The Crisis, Or It Contributed To Internationalizing Crises And Deepening Their Impact. في أعقاب الحرب العالمية الثانية وعلى إثر التناقضات التي أفرزتها، تضافرت الجهود في سياق ترميم تلك الاختلالات المتعددة على مختلف الأصعدة وقد ارتكزت الإصلاحات على الفكر الليبرالي وضمن سياق  محاولات الرأسمالية لتجديد نفسها وتجاوز تلك الإشكالات ظهرت منذ ذلك الوقت ظاهرة التجمعات الاقتصادية( المؤسساتية ، الجغرافية).  وسيتم التركيز في هذا البحث على اختلاف أثر الأزمات قبل وبعد التكتل، لتحديد إذا ما شكّل التكتل قوة ممانعة للأزمة، أم أنه ساهم في تدويل الأزمات وتعميق أثرها.